Structural neuroimaging of social cognition in progressive non-fluent aphasia and behavioral variant of frontotemporal dementia - Couto, Blas; Manes, Facundo; Montañes, Patricia; Matallana, Diana; Reyes, Pablo; Velázquez, Marcela; Yoris, Adrián; Baez, Sandra; Ibanez, Agustin (Frontiers in Human Neuroscience, 2013)
Social cognition impairments are pervasive in the frontotemporal dementias. Nevertheless, these deficits would be triggered by (a) more basic deficits in emotion and face recognition as well as by (b) higher level theory of mind processes (ToM). Both emotional processing and social cognition impairments have been previously reported in the behavioral variant of FTD (bvFTD) and also in progressive non-fluent aphasia aphasia (PNFA). However, no neuroanatomic comparison between these FTD variants has been performed. We report selective behavioral impairments of face recognition, emotion recognition and ToM in patients with bvFTD and PNFA when compared to controls. Voxel-based morphometry (VBM) shows a classical impairment of mainly orbitofrontal (OFC) anterior cingulate (ACC) insula and lateral temporal cortices. Comparative analysis of regional gray matter related to social cognition deficits (VBM) reveals a differential pattern of fronto-insulo-temporal atrophy in bvFTD and an insulo-temporal involvement in PPA group. Results suggest that in spite of similar social cognition impairments reported in bvFTD and PNFA, the former presents an inherent ToM affectation whereas in the PNFA the ToM deficit could be related to other more basic processes of face and emotion recognition. These results are interpreted in the frame of the fronto-insulo-temporal social context network model (SCNM).